2020
DOI: 10.18553/jmcp.2020.26.3.275
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Lupus Flare Symptoms Are Associated with Worsened Patient Outcomes and Increased Economic Burden

Abstract: BACKGROUND: Lupus flares significantly contribute to health resource utilization and hospitalizations. Identification of flare activity may be hindered since validated assessment scales are rarely used in clinical practice and flare severity may fall below clinician-assessed thresholds. Therefore, patient-reported outcomes of lupus flare frequency are important assessment tools for lupus management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 19 publications
1
26
1
Order By: Relevance
“…18 19 In 2010, 4 69.5% reported that lupus had affected their career versus 65.8% in 2020; of those, 29.4% reported the need to work flexible hours in 2010 versus 31.9% in 2020. Similar results have been shown in large US studies, [20][21][22] also showing a relationship between disease activity and work productivity loss, as well as with activity impairment. This yielded generally high levels of anxiety about the future in this survey.…”
Section: Impact Of Sle On Studies Work and Family Lifesupporting
confidence: 89%
“…18 19 In 2010, 4 69.5% reported that lupus had affected their career versus 65.8% in 2020; of those, 29.4% reported the need to work flexible hours in 2010 versus 31.9% in 2020. Similar results have been shown in large US studies, [20][21][22] also showing a relationship between disease activity and work productivity loss, as well as with activity impairment. This yielded generally high levels of anxiety about the future in this survey.…”
Section: Impact Of Sle On Studies Work and Family Lifesupporting
confidence: 89%
“…As well as contributing to organ damage, flares can also significantly impact health-related quality of life and place an economic burden on patients with SLE. 29,30 Increased flare frequency is associated with lower scores in general health and physical function, as assessed using the Medical Outcome Short Form 36 Health Survey. 31,32 Specifically, musculoskeletal flares have been independently associated with bodily pain and decreased physical function, social function, and physical health.…”
Section: Discussionmentioning
confidence: 99%
“…SLE flare frequency is also associated with poor health outcomes as measured by increased hospitalizations, activity impairment, and work absenteeism with lowered work productivity. 29 In addition, health care costs directly relate to flare frequency and severity, with severe flares incurring greater costs than mild or moderate flares. 29,30,33,34 Flare prevention may therefore be predicted to reduce associated direct and indirect health care costs and to improve health-related quality of life for patients with SLE.…”
Section: Discussionmentioning
confidence: 99%
“…In the long term, both disease flares and oral glucocorticoid use have been linked to organ damage, which itself increases mortality ( 22 , 23 , 24 , 25 , 26 ). Flares are also associated with reduced health‐related quality of life, and flare severity together with oral glucocorticoid use correlate with health care costs ( 27 , 28 , 29 , 30 , 31 ). A key SLE treatment goal therefore is to prevent flares while minimizing oral glucocorticoid exposure, which in turn is expected to reduce medical resource utilization ( 27 , 28 , 29 , 30 , 32 , 33 ).…”
Section: Discussionmentioning
confidence: 99%